Effect of feeding a diet with half of the recommended levels of all vitamins on the natural and inducible levels of cytotoxic activity in mouse spleen cells. - Saxena, Q B (1984)
Groups of 6-week-old female C57Bl/6 mice were fed a normal diet with recommended levels of all vitamins or a vitamin-deficient (VD) diet containing half of the recommended level of each vitamin. At different time periods (1-11 weeks) after the initiation of diets, basal natural killer (NK) activity, interleukin-2 (IL-2) and concanavalin A (Con A)-induced cytotoxic activity, Con A-induced IL-2 production and levels of allospecific cytotoxic T cell activity generated in a mixed lymphocyte culture (MLC), were studied in spleen cells derived from control and VD mice. Results indicated that: (i) spleen NK activity remained normal until 2 weeks after the initiation of VD diet, fell steeply to low levels at the 4 and 5 week time points and remained depressed thereafter; (ii) IL-2- and Con A-induced levels of cytotoxic activity in spleen cells derived from VD mice declined at 4 weeks after the institution of VD diet, and then remained low throughout the study; (iii) the capacity of spleen cells from VD mice to generate IL-2 in response to Con A and cytotoxic T cells in response to allogeneic spleen cells, was normal at 1 and 4 weeks after initiation of the VD diet and was markedly depressed at the 6 and 9 week time points. These results suggest that partial combined deficiencies of dietary vitamins strongly influence assays of immune function.